2009
DOI: 10.2166/wh.2009.141
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors in the occurrence of injured coliforms in the drinking water distribution system in the city of La Plata, Argentina

Abstract: The objective of this study was to evaluate the influencing factors in the occurrence of coliforms Klebsiella oxytoca in winter and spring. Significant correlations were observed between coliforms and the distance from the initial treatment point, and with the level of free chlorine. We conclude that drinking water contamination in La Plata occurs in the distribution system due to increased temperatures and reduced disinfectant levels, which result in bacterial regrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Bacterial growth in bulk water can be fostered by long residence times that result in the decay of disinfectant residuals, elevated temperatures, and stagnation. Given the shortened supply periods in IWS systems, residence times of bulk supply are likely low; microbial growth in this phase may then be less of a concern in many IWS than in most CWS systems (although IWS systems with long supply cycles would behave similarly to CWS systems). There have not been any studies of growth in IWS systems.…”
Section: Biofilms Loose Deposits and Microbial Growthmentioning
confidence: 99%
“…Bacterial growth in bulk water can be fostered by long residence times that result in the decay of disinfectant residuals, elevated temperatures, and stagnation. Given the shortened supply periods in IWS systems, residence times of bulk supply are likely low; microbial growth in this phase may then be less of a concern in many IWS than in most CWS systems (although IWS systems with long supply cycles would behave similarly to CWS systems). There have not been any studies of growth in IWS systems.…”
Section: Biofilms Loose Deposits and Microbial Growthmentioning
confidence: 99%
“…Bacterial regrowth has been observed under the diminished presence of disinfectant residuals (i.e., chlorine and chloramine), which is influenced by the complex interactions between chemical and physical parameters including but not limited to temperature, alkalinity, pH, organic matter/humic substances, phosphate, and pipe materials, etc. (5,20,27,42). The chemical disinfection reaction with organic matter can also lead to an increase in assimilable organic carbon (AOC) (10,22,33) and other chemicals termed disinfection byproducts (DBPs) (32).…”
mentioning
confidence: 99%
“…The removal and monitoring of microorganisms can avoid disease outbreaks caused by the presence of pathogens in the water. Previous report demonstrated that the proportion of injured coliforms fluctuated between 70 and 100% in the test samples of the chlorine disinfection drinking water distribution system (Córdoba et al 2010), while those in water samples from filtered backflow of drinking water and damaged municipal pipelines accounted for up to 90% (Bissonnette et al 1975;Means et al 1981). Ray (1979) believed that the permeability barrier of injured cells is impaired, which makes them more susceptible to structural injury caused by various selective compounds.…”
Section: Existence and Threat Of Disinfectant-injured Bacteriamentioning
confidence: 99%